Analisis Kesalahan Berbahasa Indonesia Postingan Instagram Kominfo Padangpanjang: Kajian Sintaksis - Ratna Sari Dewi Pohan; Laila Fitri; Fatma Zakia (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The problem behind this research is the large number of errors in Indonesian when writing posts on social media. Effective sentences are one of the mistakes that are often encountered on social media. Mistakes in using effective sentences on social media have an influence on posts. Many people don't know about effective sentences on social media, effective sentences play an important role on social media, even in posts. This is the cause of effective sentence errors being chosen as the research object. This research aims to analyze Indonesian language errors in sentences on Kominfo Padangpanjang's Instagram posts. The type of method used in the research is a descriptive qualitative method. Data collection methods and techniques in this research are observation methods and documentation techniques. The data analysis technique in this research is using the intralingual matching method. The analysis steps are carried out in stages 1) reading Kominfo Padangpanjang's Instagram posts dated 1-15 June 2024, 2) tabulating Kominfo Padangpanjang's Instagram post data, 3) classifying Kominfo's Instagram post data Padangpanjang, 4) analyzing data, and 5) conclusions. Based on the analysis results obtained in this research, sentence errors are effective in the aspects of straightforwardness, accuracy, clarity, economy and alignment. Based on errors found, 59 data were found. Based on the classification, 15 data were found for straightforwardness, 3 data were found for accuracy, 11 data were found for clarity, 18 data were found for frugality, and 13 data were found for parallelism.